2016
DOI: 10.1530/ec-16-0070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on health status in non-vitamin D deficient people with type 2 diabetes mellitus

Abstract: ObjectiveIncreased levels of depressive symptoms, fatigue or pain (all dimensions of reduced health-related quality of life (HRQOL)) are common in people with type 2 diabetes mellitus (DM). Earlier studies have reported associations between low vitamin D status and fatigue and depressive symptoms. The aim of the present study was to examine the effects of vitamin D supplementation on dimensions of HRQOL in people with type 2 DM.DesignRandomised, double-blind, placebo-controlled trial.MethodsThe effect of month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 30 publications
0
21
1
Order By: Relevance
“…Concerning previous studies in diabetic patients, Krul-Poel et al recently reported the results of a cross-sectional study that showed the absence of an association between vitamin D levels and HRQoL in non-vitamin D deficient Dutch subjects with T2DM [ 21 ]. Similarly, in an intervention study, the same research group could not show any improvements after six months of vitamin D supplementation (cholecalciferol 50,000 IU/month versus placebo) in patients who had T2DM with considerable associated comorbidities (micro- and macrovascular complications) [ 22 ]. In another intervention trial, Mager et al reported that both daily (2000 IU/D) and monthly (40,000 IU/month) supplementation with vitamin D 3 only correlated to a slight increase in the scores of the health-related quality of life questionnaire Short Form 36 Health Survey in elderly Canadian participants (95% with T2DM) with long-term diabetes duration (7–20 years) and chronic kidney disease [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning previous studies in diabetic patients, Krul-Poel et al recently reported the results of a cross-sectional study that showed the absence of an association between vitamin D levels and HRQoL in non-vitamin D deficient Dutch subjects with T2DM [ 21 ]. Similarly, in an intervention study, the same research group could not show any improvements after six months of vitamin D supplementation (cholecalciferol 50,000 IU/month versus placebo) in patients who had T2DM with considerable associated comorbidities (micro- and macrovascular complications) [ 22 ]. In another intervention trial, Mager et al reported that both daily (2000 IU/D) and monthly (40,000 IU/month) supplementation with vitamin D 3 only correlated to a slight increase in the scores of the health-related quality of life questionnaire Short Form 36 Health Survey in elderly Canadian participants (95% with T2DM) with long-term diabetes duration (7–20 years) and chronic kidney disease [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning diabetes, a recent cross-sectional study in non-vitamin D deficient Dutch subjects, with fair metabolic control of their T2DM, found no association between vitamin D levels and HRQoL [ 21 ]. Similarly, in a randomised, double-blind, placebo-controlled trial, the same researchers showed that there was no effect of vitamin D supplementation (50,000 IU for six months) on self-reported HRQoL, which was assessed using the Short Form 36 Health Survey, in patients with similar characteristics [ 22 ]. Meanwhile, Mager et al analysed the impact of six months of different doses of vitamin D3 supplementation (2000 IU/daily or 40,000 IU/monthly), administered to Canadian adults with diabetes mellitus (more than 95% with T2DM) and other chronic diseases, on the following primary outcomes: vitamin D status, bone health and Fibroblast Growth Factor-23, and on the following secondary outcome: HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we confirmed VDR‐dependent 1,25(OH)2D3 is able to counteract LPS‐induced overexpressions of cytokines through regulating NF‐ κ B signaling pathway in vitro . Currently, vitamin D treatment has been employed in many illnesses (Westra et al , ; Yakoob et al , ), but remains to be not involved in OLP. Our findings make vitamin D management a potential and promising approach for OLP administration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a case-report study with one Type-1 patient suffering from diabetic neuropathy, mentioned an improvement after correction of his vitamin D3 deficiency following supplementation of 50,000 UI/week for 4 weeks (Bell, 2012). On the other hand, an interventional randomized double-blind placebo-controlled trial in non-vitamin D-deficient patients with Type 2 diabetes, showed that vitamin D3 supplementation of 50,000 UI/week for 6 months provided no improvement of diabetic neuropathy (Westra et al, 2016). Placebo-controlled multi-centric studies are required to assess the role of vitamin D3 supplementation on diabetic neuropathies (Valensi et al, 2005).…”
Section: Vitamin D3 In Neurological Disordersmentioning
confidence: 99%